Introduction to the Special Issue on Transitioning to Blended Learning - Picciano, Anthony G (Online Learning, 2011)
In 2004, the Alfred P. Sloan Foundation funded an invitation-only workshop on blended learning. It was one of the first such events to focus entirely on the concept of combining online and face-to-face instruction into a new instructional modality and since has evolved into the Annual Sloan Consortium Blended Learning Conference and Workshop. Over the past seven years, this Conference and Workshop has added significantly to the research base and best practices that apply to blended learning. Its scholarly production includes a plethora of important studies and resources that have contributed significantly to what is known about blended learning. For example, the work of this Conference and Workshop has produced: • a comprehensive look at a definition of the term “blended learning”; • the first book dedicated entirely to the research on blended learning [1]; and • an extensive review of blended learning instructional models. [2] In April 2010, the 7th Annual Sloan Consortium Blended Learning Conference and Workshop attracted almost three hundred educational leaders, faculty members, instructional designers and researchers who discussed, shared and considered effective practices in the design and delivery of blended learning environments. The purpose of this special edition of the Journal of Asynchronous Learning Networks is to preserve some of the knowledge and insights shared at this event. The articles selected also represent well the theme of this special edition – transitioning to blended learning.